Alexander Blok as a reader of courtly literature: the origin of some motifs and characters in the drama "The Rose and the Cross" - Maria Efimova (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article studies mediaeval sources of The Rose and the Cross that influenced the representation of the imagery of the mediaeval world in this text. It gives a review of relevant literature on this topic and demonstrates, among other things, that Blok’s notes and marginalia in the numerous books of his home library allow us to examine the development of the idea and the material of the play within the context of the literary sources and prototypes. In this regard, the article gives a translation and analysis of Blok’s notes and marginalia, especially those neglected in the previous research, in the text of the Provençal romance Flamenca, the Lancelot- Grail cycle and other oeuvres of mediaeval literature, as well as in the research literature on this topic from Blok’s home library. The Russian text of some notes is published for the first time here; they make it possible to study the issue of their infl uence on the development of the characters in diff erent editions of the play because they refer not only to their direct or implicit literary prototypes, but to the numerous topoi and mythologemes of mediaeval culture. The adoption of these literary sources to the plot and the imagery of the play refl ects the poet’s attempts to comprehend and analyse the courtly literature, which signifi cantly enriched the content of the play. Introducing the description of Blok’s notes and marginalia, the article studies the possible infl uence of different mediaeval literary traditions on the poetic discourse and its evolution in various editions of The Rose and the Cross. The method of comparative analysis of mediaeval texts and of the text of the play allowed us to reevaluate the depth of some images and motifs in The Rose and the Cross. The conclusion of the article is that due to a synthesis of fragmented images and details, Blok created an independent and selfcontained literary reality.